Regional anesthetic techniques for the thoracic limb and thorax in small animals: A review of the literature and technique description. (November 2018) - Portela, D.A.; Verdier, N.; Otero, P.E.
Highlights: Overview of the literature on peripheral nerve blocks of thoracic limb in dogs and cats. Use of nerve stimulation and ultrasound guided nerve blocks of the thoracic limb. Overview of the literature on thoracic paravertebral block in dogs. Use of nerve stimulation and ultrasound guided nerve blocks for thoracic paravertebral blocks in dogs. Graphical description of peripheral nerve blocks guided by nerve stimulation and ultrasound. Abstract: Veterinary regional anesthesia (RA) has been rapidly increasing in popularity over the last 10 years, as evidenced by the increasing amount of literature available and the continuous development of new techniques in small animals. The introduction of new technologies such as nerve stimulation and ultrasound (which increased the objectivity and precision of the procedure) and the promising beneficial perioperative effects conferred by RA are encouraging clinicians to incorporate these techniques in their daily perioperative anesthetic and analgesic animal care. However, there is a lack of consensus regarding outcomes when RA is used, as well as outcome comparisons between regional anesthetic techniques. Further large-scale clinical studies are still necessary. This article is the first part of a two-part review of RA in small animals, and its aim is to discuss the most relevant studies in the veterinary literature, where objective methods of nerve location have been used, and to illustrate in pictures the currently used techniques for providing RA to the thoracic limb and the thorax in small animals.